Conception of Money in Islamic Economic Dimension - Ismi Yonifia (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2021)
Money is seen not only as a legal tender (legal tender) but also seen as a commodity, money has two possibilities, namely the possibility leads to the good thing and the possibility leads to the bad thing. Both depend on the person using it. Money continues to innovate and evolve from cash to non-cash or electronic money. The emergence of crypto currencies raises pros and cons in various circles. This study aims to explain the concept of money from an Islamic perspective by analyzing crypto currencies as virtual currency. The writing method used is qualitative research using a literature review. The data taken are secondary data and data collection techniques using documentation and library studies. The results of this study explain that in Islamic economics currency must have underlying assets recognized by the government to avoid